2009
DOI: 10.1007/s11483-009-9108-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of the ι-Carrageenan/Maltodextrin/Water System at Different Potassium Chloride Concentrations and Temperatures

Abstract: Equilibrium phase diagrams of the ι-carrageenan/ maltodextrin/water system have been established at potassium chloride (KCl) concentrations of 0.1, 0.2, and 0.3 M and 80, 85 and 90°C. All pseudo-binary phase diagrams of ι-carrageenan/maltodextrin mixtures suggested classic segregative phase separation. The binodal was heavily skewed toward the maltodextrin axis. The high asymmetry of the ι-carrageenan/maltodextrin/water phase diagram determined by the phase-volume-ratio method was consistent with the compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…with MD and the structures have been described as MD aggregates within pores of the gellan network (Clark et al, 1999;Kanyuck et al, 2021a). Phase separated networks are known to form with gelatin (Kasapis et al, 1993a), agarose (Loret et al, 2005), and carrageenan (Wang and Ziegler, 2009;Gładkowska-Balewicz, 2017). Additionally, gelatin melted at the measurement temperature (37 °C).…”
Section: Gelling Agentsmentioning
confidence: 99%
“…with MD and the structures have been described as MD aggregates within pores of the gellan network (Clark et al, 1999;Kanyuck et al, 2021a). Phase separated networks are known to form with gelatin (Kasapis et al, 1993a), agarose (Loret et al, 2005), and carrageenan (Wang and Ziegler, 2009;Gładkowska-Balewicz, 2017). Additionally, gelatin melted at the measurement temperature (37 °C).…”
Section: Gelling Agentsmentioning
confidence: 99%
“…MD has been studied in mixed gelling systems previously, and most often for applications in fat reduction due to the creaminess mimicking abilities of MDs (Chronakis, 1998). Most literature has proposed phase separated mixed gels between a low DE MD and gelatin (Kasapis et al, 1993a;Lorén and Hermansson, 2000), low methoxy pectin (Picout et al, 2000), agarose (Loret et al, 2006), iota carrageenan (Wang and Ziegler, 2009), milk protein (Chronakis et al, 1996), locust bean gum, gum acacia, and high salt carboxymethyl cellulose (Annable et al, 1994). For charged polymers, phase separation was either not observed with high methoxy pectin (Evageliou et al, 2000) or was only observed at sufficient levels of added salts with carboxymethyl cellulose (Annable et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The polymers concentration effect on phase separation was largely studied, and it was described as follows: At low polymer concentration, the polymers can coexist in a single phase, but when the polymer concentration increases, phase separation occurs. 13 As food processing is often based on solvent removal (solute concentration increase) and as biopolymers are common components in food systems, phase separation is expected to have an important role in the tuning of food properties. 14 For instance, phase segregation induced by freeze-drying has been reported.…”
Section: Introductionmentioning
confidence: 99%